2014
DOI: 10.1007/s12565-014-0242-1
|View full text |Cite
|
Sign up to set email alerts
|

Metrical analysis of dromedary digital bones

Abstract: Dromedary camels are large even-toed ungulates which are well adapted to life in large deserts. Examinations of their feet have revealed many structural peculiarities. We have measured the digital bones of the dromedary in order to determine whether there are morphometric variations in the digital bones between the lateral and medial sides in individual limbs and/or in the right and left thoracic and pelvic limbs, with the aim to clarify whether there are anatomical differences in the digital bones of dromedar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
3
3
0
1
Order By: Relevance
“…In camels, IA injection of the coffin joint was performed with the needle inserted distally in the ventrolateral or ventromedial direction and perpendicular to the bearing surface of the foot. The optimal landmarks established in this study are similar to those previously established in the camel forelimb coffin joint [15,24,25]. However, in horses and cattle, the proper site for puncturing the coffin joint is proximal to the coronary band with the needle directed toward the extensor process of the 3 rd phalanx [22,26].…”
Section: Number Of Attemptssupporting
confidence: 59%
“…In camels, IA injection of the coffin joint was performed with the needle inserted distally in the ventrolateral or ventromedial direction and perpendicular to the bearing surface of the foot. The optimal landmarks established in this study are similar to those previously established in the camel forelimb coffin joint [15,24,25]. However, in horses and cattle, the proper site for puncturing the coffin joint is proximal to the coronary band with the needle directed toward the extensor process of the 3 rd phalanx [22,26].…”
Section: Number Of Attemptssupporting
confidence: 59%
“…The 3D reconstruction of the bones demonstrated all the structures of the digit bones and explained the bones of the lateral and medial sides, the right and left limbs of the same leg were nearly similar in size. The current study indicated that from the measurements of the phalanges, the left side had a slight increase in values over the right side while the lateral sides had higher values than the medial sides [ 5 7 ].…”
Section: Discussionmentioning
confidence: 95%
“…This interspecies anatomical difference in the length of phalangeal bones was thought to be one of the adaptive structures to be connected to the capacity for shock absorption during locomotion; longer and larger bones have a greater capacity than shorter and slender bones to absorb shock (impact energy). The capability to absorb mechanical shock appears to help the camel adapt to a dry desert environment by reducing the energy expenditure (mechanical requirements) of its locomotor mode (Alrtib et al., 2013; Janis, Theodor, et al., 2002; Muggli et al., 2011; Nourinezhad et al., 2015; Ocal et al., 2004).…”
Section: Discussionmentioning
confidence: 99%